Spontaneous isolated bladder rupture following normal delivery - Diana, Valsa; K., Bhargavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Spontaneous bladder rupture in a primipara after normal delivery within the first week of puerperium is a rare surgical emergency. The importance of suspecting and recognizing the voiding dysfunction in the postpartum period and early catheterisation to prevent such catastrophe is highlighted in this case report. We report a case of spontaneous intraperitoneal bladder rupture in a 26 year old primipara 3 days after normal delivery of a 3kg baby with episiotomy